Opak-Progo watershed’s potential for geography experiential learning - Mukminan Mukminan; Arif Ashari; Suhadi Purwantara; Dyah Respati Suryo Sumunar (Universitas Negeri Malang, 2024)
The implementation of learning innovation is crucial for 21st-century education, particularly for Generation Z and Alpha students. Additionally, experimental learning (EL) is highly beneficial for learning geography, especially on the topic of geography research. This study evaluates the potential of the Opak and Progo Watersheds as a geography laboratory. This research was conducted with a spatial approach. Data were collected by observation, literature study, interpretation of remote sensing imagery, and documentation. The garnered data were analyzed by matching, scoring, and statistical analysis. A descriptive analysis was performed to support these analyses. The results show that the Opak and Progo watersheds have the potential for learning geography. This potential is inseparable from its heterogeneity of geological, geomorphological, meteorological, and hydrological conditions. The upstream area presents more potential because it has more complex conditions, indicated by the significant difference between the upstream and downstream areas in each watershed, as well as the variation between the four sample locations covering the two watersheds. In sum, this study offers novel insights into the potential of the area for natural laboratories for geography studies, especially the laboratories based on watersheds. This study also provides alternative information regarding watershed areas as a geography learning resource.